2002
DOI: 10.1046/j.1445-2197.2002.02400.x
|View full text |Cite
|
Sign up to set email alerts
|

Total thyroidectomy is now the preferred option for the surgical management of Graves’ disease

Abstract: Given that subtotal thyroidectomy provides an unpredictable outcome and that the risk of permanent complications is no greater than with total thyroidectomy, there appears little logical reason to continue to recommend subtotal thyroidectomy for the surgical management of Graves' disease. We believe that Graves' disease should join the increasing list of thyroid conditions for which total thyroidectomy is the preferred option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
4
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 22 publications
3
56
4
6
Order By: Relevance
“…Analyzing our series of patients we did not find any significant differences in relation to gender in comparison to other authors [13,16] . The average age of the patients was 29 years (15 to 75) which is slightly higher than data available in literature [2,16] . In the US, the number of patients with GD that are surgically treated is small.…”
Section: Resultscontrasting
confidence: 77%
See 1 more Smart Citation
“…Analyzing our series of patients we did not find any significant differences in relation to gender in comparison to other authors [13,16] . The average age of the patients was 29 years (15 to 75) which is slightly higher than data available in literature [2,16] . In the US, the number of patients with GD that are surgically treated is small.…”
Section: Resultscontrasting
confidence: 77%
“…Due to a relatively low rate of complications for TT, com-pared to less extensive procedures, many authors recom-mended TT as the treatment of choice for GD [16,[19][20][21] . In our study the most common indication for surgery was thyromegaly (80%), followed by ophthalmopathy and ultrasound diagnosed thyroid nodule >1 cm (10%).…”
Section: Resultsmentioning
confidence: 99%
“…26,27 Nevertheless, the above approach has recently been challenged by endocrine surgeons who support total thyroidectomy and have demonstrated better control of thyroid disease and even comparable morbidity to subtotal thyroidectomy. [28][29][30][31] Due to these encouraging reports, total thyroidectomy has gained acceptance among the surgeons of our institution and over the last few years it has rapidly displaced the more conservative surgical approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, it has been shown that the morbidity and cosmetic impact of cervical incision after total thyroidectomy are comparable to those of subtotal thyroidectomy. [7][8][9] Recently, minimally invasive surgery has been successfully used for the treatment of both benign and malignant thyroid disorders. The well-known advantages of this approach are the reduced postoperative pain, improved cosmesis (patients are usually young females), shorter hospital stay, and lower costs.…”
Section: Introductionmentioning
confidence: 99%